Core/shell fibers of Carboxymethylcellulose/Poly(lactic acid) loaded with Curcumin. - León Pérez, Jadileyg Gabriela; Estrada Villegas, Gethzemani Mayeli; Morales-Corona, Juan; Olayo-Gonzalez, Roberto; Olayo-Valles, Roberto (Universidad Pedagógica y Tecnológica de Colombia, 2020)
To dose curcumin (Cur) while avoiding its degradation, a polymeric material consisting of fibers with core/shell structure was designed. Coaxial electrospinning allowed us to obtain fibers with poly(lactic acid) (PLA) core, and carboxymethylcellulose (CMC) shell. CMC/PLA fibers were compared with conventional PLA fibers. Scanning electron microscopy images allowed us to characterize the core/shell structure of CMC/PLA-Cur fibers. The presence of Cur in the fibers was confirmed by Raman spectroscopy. Thermogravimetric analysis and differential scanning calorimetry showed the effect of Cur on the thermal behavior of the fibers, and showed contrasting behavior between CMC/PLA and PLA fibers. Cur release experiments were performed at physiological pH and the results were fitted with the Korsmeyer-Peppas model. The release rate of CMC/PLA fibers was significantly lower than that of PLA fibers.